2020
DOI: 10.3390/ani10071155
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Performance of Suckling Piglets Provided Three Supplemental Heat Sources

Abstract: This study compared water-heated mats (WM) and electric-heated mats (EM) with heat lamps (HL) as supplemental heat sources for suckling piglets. Forty-two litters were studied in 3 trials. In all trials, behavior of piglets was video-recorded on day 1, 3, 7, 14, and 21 postpartum. Videos were scan-sampled to register postures (lying and standing) and locations (on or away from mat) to assess piglet use of heat sources. Litter size and weight at birth and weaning, and pre-weaning mortality were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Piglets are naturally motivated to stay near their dam and littermates several days after farrowing to receive protection, warmth, and nutrition [15][16][17][18]. Pigs are attracted to their dam's udder immediately following birth [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Piglets are naturally motivated to stay near their dam and littermates several days after farrowing to receive protection, warmth, and nutrition [15][16][17][18]. Pigs are attracted to their dam's udder immediately following birth [19].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in heat source locating time might be explained by the way these heat sources function. Zhu et al, [ 15 ] reported that lamps radiate heat in a top-down pattern, which warms standing piglets better than lying piglets. Davis and others [ 13 ] reported that mats provide a more evenly distributed surface temperature and are considered bottom-up heating with their function to heat piglets through their stomachs, which may increase the desire to lie down.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of the following four options of heating system for prenursery pigs was experimentally evaluated: electrically heated mat (EM), water-heated mat (WM), water-heated 'warm' floors (FH), and infrared heating lamps (IRL). Based on the research results, taking into account statistical data on average daily gain (ADG), mortality rate of prenursery pigs, as well as the effect of heating on their behavior, use of electrically heated mats or 'warm' floors with water heating were considered the most effective local heating system within the period of the first five weeks (starting from the third week) [22][23][24][25][26][27]. A carbon fiber heater has been developed for the local heating of breeding saw with prenursery pigs, providing the required thermal comfort and reducing power consumption compared to conventional heating lamps (HL) [28].…”
Section: Introductionmentioning
confidence: 99%